Laparoscopic rectopexy is feasible and safe in the emergency admission setting. (October 2015) - Bloemendaal, A. L. A.; Mishra, A.; Nicholson, G. A.; Jones, O. M.; Lindsey, I.; Hompes, R.; Cunningham, C.
Abstract Aim External rectal prolapse may require emergency admission in the elderly and comorbid population. We report the safety and efficacy of laparoscopic ventral rectopexy in patients having an emergency admission with external rectal prolapse. Method A retrospective analysis was performed of a prospective database of all rectopexies performed from 2006. Outcome and follow‐up data were assessed. Results Of 812 rectopexies performed, 28 were included for analysis. The mean length of hospital stay was 13.0 days. All operations were completed successfully and without intra‐operative complications. Four patients developed a postoperative complication. Two patients developed a recurrence of prolapse. Conclusion Laparoscopic correction of rectal prolapse following emergency admission is both feasible and safe. It can be considered for both recurring cases and cases with multiple comorbidities.